An apolar world: Anarchic and violent - De Rivero Barreto, Oswaldo (2020)
This article supports the apolar structure of the current world in which we live, with anarchy aggravated by the COVID-19 pandemic, as well as by the effects of global warming. Likewise, the author presents four proposals to face the health crisis, as well as the realism with which Peru must direct its foreign policy.